Lipid photosensitizers for suppression of gastric inhibitory polypeptide in obese with type 2 diabetes. (July 2020) - Lee, Sanghee; Na, Kun
Abstract: "K-cell targeted photodynamic therapy (K-cell targeted PDT)" with a minimally invasive procedure was investigated to reduce the secretion of gastric inhibitory polypeptide (GIP), an incretin hormone secreted from enteroendocrine K-cells in the duodenum that is suspected to be strongly correlated with obesity. Oleic acid-poly (ethylene glycol)-chlorin e6 (OA-PEG-Ce6, OPC) was designed for PDT because it targets K-cells through the interaction of OA in OPC with a G protein-coupled receptor (GPR 119) that is overexpressed on K-cells and mediates fatty acid sensing. OPC interacted with duodenal cells (HUTU-80) expressing GPR 119 and HEK 293 cells transfected with human GPR 119 to mimic K-cells in vitro . The intracellular intensity and cytotoxicity of OPC on HUTU-80 cells increased 5- and 3-fold compared to PEG-Ce6, respectively. In particular, its intensity on HEK 293 cells overexpressing GPR 119 showed 7.8-fold higher than that of PEG-Ce6. Moreover, in high fat-diet animal models, OPC induced endocrine cell death through PDT, resulting in a decrease in the plasma GIP level and a reduction their weight (80% less than on the day of PDT initiation). Therefore, K-cell targeted PDT presents a new direction of future minimally invasive anti-obesity treatment to replace conventional methods such as bariatric surgery and radiofrequency ablation. Graphical abstract: An Oleic acid (OA) conjugated polymeric photosensitizer (PS) was developed for efficient endoscopic K-cells targeted photodynamic therapy (PDT) to treat obesity and type 2 diabetes. K-cells secret gastric inhibitory polypeptide (GIP) and GIP is strongly correlated with forementioned metabolic diseases. K-cell targeted PDT enabled restoring of metabolic diseases by modifying the balance of hormones with minimally invasive to surrounding cells. Image 1